False Competition and Fulfilling the Promise of Retail Wheeling - Mitchell, James (Maine Policy Review, 1995)
In the past few years,Maine’s electric utilities have begun to face the forces of competition.Maineis experiencing the effects of a national trend, a shift from a traditional and regulated system to a more innovative and competitive one. James F. Mitchell describes some of the political and financial limits to restructuring and provides suggestions for how to proceed in creating full and fair competition. This article is taken from the author’s presentation at a December 1994 conference entitled ”Retail Wheeling,” sponsored by the Margaret Chase Smith Center for Public Policy’s Project for the Study of Regulation and the Environment.